SUBALTERN CHRISTIAN GROUPS AND THE CRISIS OF CULTURAL IDENTITY: A Case Study Of Christian Pulaya of North Kerala - Pallath, J J (Journal of Dharma, 1999)
Subaltern cultures are ways of life at home on Earth and affirm the experience of body and emotion. In general they have an ecological spirituality, a somatic philosophy, an egalitarian value system and a feminine world view. They do not denigrate the body or the ordinary, mundane, everyday facts of life but rather they celebrate these things and in doing so, intersect with many of the most vital interests of the post modem culture.